The private and fiscal returns to schooling and the effect of public policies on private incentives to invest in education : a general framework and some results for the EU - Angel De la Fuente; Juan F. Jimeno (Center for Economic Studies and ifo Institute (CESifo), 2005)
This paper develops a comprehensive framework for the quantitative analysis of the private and fiscal returns to schooling and of the effect of public policies on private incentives to invest in education. This framework is applied to 14 member states of the European Union. For each of these countries, we construct estimates of the private return to an additional year of schooling for an individual of average attainment, taking into account the effects of education on wages and employment probabilities after allowing for academic failure rates, the direct and opportunity costs of schooling, and the impact of personal taxes, social security contributions and unemployment and pension benefits on net incomes. We also construct a set of effective tax and subsidy rates that measure the effects of different public policies on the private returns to education, and measures of the fiscal returns to schooling that capture the long-term effects of a marginal increase in attainment on public finances under conditions that approximate general equilibrium.
Keywords: I28; I22; I20; 330; Bildungsinvestition; Bildungsertrag; Steueraufkommen; Bildungspolitik; Ökonomischer Anreiz; Schätzung; EU-Staaten